Positioning Nutrition with Universal Health Coverage : Optimizing Health Financing Levers - Subandoro, Ali Winoto; Okamura, Kyoko; Mehta, Michelle; Wang, Huihui; Ahluwalia, Naina; Finkel, Elyssa; Bulungu, Andrea L.S.; Dinsa, Girmaye; Okara, Latifat; Wilson, Shelby (World Bank, Washington, DC, 2022)
Achieving universal health coverage (UHC) is a top global priority, and nutrition actions are a critical part of meeting that goal. When delivered within key windows of opportunity to improve health throughout the life-course, essential nutrition actions play an important role in reducing the burden of disease and preventing permanent physical and cognitive impairments, ultimately staving off future health care costs for both individuals and health systems. Coverage and quality of nutrition service delivery remains low, despite robust evidence of cost-effective interventions. The health system, and most especially primary health care (PHC), is essential for delivering high-impact, cost-effective, nutrition-specific interventions at scale. There are gaps in knowledge on how to deploy resources more effectively to improve the delivery of nutrition services as part of preventive and promotive health care. A shift in focus is needed from the “what” and “why” of scaling-up nutrition to the “how” of improving nutrition services coverage and quality of nutrition services delivered through the health system, and especially PHC. Parts 1, 2, and 3 of this paper introduce the thesis that health financing arrangements can be optimized to ensure that distribution and utilization of health system resources are aligned with nutrition objectives. Parts 4, 5, and 6 of the paper explore the financing challenges and options to address key financing and service delivery challenges.